FRI0057 Synovial angiogenesis is mediated through notch signaling pathways. (23rd January 2014) - Gao, W.; Sweeney, C.; Walsh, C.; Rooney, P.; McCormick, J.; Fearon, U.; Veale, D.J.
Abstract : Background: Angiogenesis plays a crucial role in the formation and maintenance of the pannus in inflammatory arthritis. The Notch signaling pathway is critical for vascular angiogenesis and endothelial cell (EC) fate; however the mechanisms involved in regulating these processes in the inflamed joint remain to be elucidated. Objectives: To examine if Notch signaling pathways mediate Vascular Endothelial Growth Factor (VEGF) and Angiopoietin 2 (Ang2)-induced vascular function in the inflamed joint. Methods: Whole tissue synovial biopsies obtained at arthroscopy and human microvascular endothelial cells (HMVEC) were utilized. Notch-1 IC (intracellular domain), Notch-4 IC, Notch ligand DLL-4, downstream target genes Hrt-1 and Hrt-2 mRNA and/or protein expression was measured by Real-time PCR and/or Western Blot. VEGF/Ang2 induced EC function was assessed using transwell invasion chambers, matrigel tube formation assays and wound repair scratch assays +/- Notch-1 siRNA or a γ-secretase inhibitor (DAPT). Pro-MMP-2/9 expression was measured by zymography. Results: Notch-1 IC and 4 IC protein expression were demonstrated in RA and PsA synovial explants with undetectable level in OA patients. VEGF and Ang2 induced Notch-1 IC and 4 IC protein expression in RA synovial explants cultures ex-vivo and HMVEC, levels of which were further potentiated following stimulation with VEGF and Ang2 in combination (p<0.05). mRNA expression of Notch-1, DLL-4 and Hrt-1 and Hrt-2 were significantly induced following stimulation with VEGF and Ang2 alone and in combination (p<0.05). VEGF-induced Notch-1 IC protein expression was completely blocked in the presence of Notch-1 siRNA (p<0.05). Furthermore VEGF/Ang2-induced EC invasion, tube formation, migration and pro-MMp-2/9 expression were inhibited in the presence of Notch-1 siRNA or DAPT (p<0.05). Conclusions: This study demonstrates Notch-1 IC and -4 IC expression in RA and PsA synovial explants. VEGF and Ang2 alone induce Notch-1 IC signaling pathways, with a synergistic increase in combination. VEGF/Ang2-indcued HMVEC function is inhibited in the presence of Notch-1 siRNA and DAPT. These results suggest that in inflammatory conditions, VEGF/Ang2-induced angiogenesis is mediated in part through Notch signaling pathways. Disclosure of Interest: W. Gao: None Declared, C. Sweeney: None Declared, C. Walsh: None Declared, P. Rooney: None Declared, J. McCormick: None Declared, U. Fearon: None Declared, D. Veale Grant/Research support from: Wyeth, GSK, Abbott, Opsona, Consultant for: Wyeth, GSK, Abbott, Pfizer, Schering Plough, Centocor, Speakers Bureau: Wyeth, GSK, Abbott, Pfizer, Schering Plough, Centocor, Mundipharma